Incorporating critical thinking and English as a medium of instruction for elementary school students - Muniroh, Siti; Rachmajanti, Sri; Laksmi, Ekaning Dewanti; Fadhillah, Jasmine Nur; Saputri, Nur Nilam Ayu (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
This case study aims to find out how teachers of the International Class Program at an elementary school in Malang incorporated critical thinking (CT) pedagogy in teaching subjects with English as a Medium of Instruction. Eighteen teachers filled in an online questionnaire, and two of them were interviewed. Analysis of one pre-recorded video for English class (lasted for 13 minutes) and one video of Math class delivered through Zoom meeting (lasted for 29 minutes) was done to investigate how teachers triggered students’ thinking in the classroom practice. Also, an analysis of three lesson plans was done to dig further information about teachers’ teaching practices. The findings indicated that the teachers have practical knowledge of CT pedagogy from reading and workshops that were not necessarily focused on CT. Textbooks were mainly used to guide the teachers’ teaching, supported by audio-visual media. Questions primarily were used to trigger students’ higher-order thinking by connecting the texts with the students’ experiences in real life. Despite the implicit policy of CT, the teachers have implemented CT strategies in the International Class Program. Overall, the teachers have played as more knowledgeable others that facilitated the students’ learning to think critically. However, they were not confident whether the teaching material they were developed supported CT pedagogy implementation. Thus, the study findings revealed their need for supervisors to evaluate the content of teaching material and practical guidance to conduct thinking routines for the young learners in the subjects with English as a medium of instruction.